A Comparative Study of the Education Systems at SDIT Labschool Al Fatah and SDN Margahayu XIX - Girah Murtiningsih (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study aims to describe and compare the curriculum design and education system implementation in an Integrated Islamic Elementary School (SDIT) as a religion-based private institution and a Public Elementary School (SDN) as a public institution. The approach adopted in this research is descriptive qualitative utilizing a comparative study method. Primary data were gathered through in-depth interviews with the Principal of SDIT Labschool Al Fatah and the quality assurance coordinator of SDN Margahayu XIX. The findings indicate that both institutions have implemented the Merdeka Curriculum as their operational foundation; however, significant disparities exist in philosophical orientation, learning concepts, and infrastructural readiness. SDIT Labschool Al Fatah employs a holistic curriculum design that integrates Islamic values and science through a student-centered learning approach, supported by comprehensive information technology (IT) facilities. Conversely, SDN Margahayu XIX focuses on the standard government general curriculum that is inclusive, applying a modified conventional (teacher-centered) method, where the primary challenges lie in limited digital infrastructure and teacher resource readiness. Although the curriculum transition process encountered obstacles such as a learning lag during the adaptation phase in both schools, this new regulation has proven effective in mapping and directing students' interests and talents. In general, this study concludes that institutional status directly shapes the characteristics, culture, and learning ecosystem in responding to national education policies.